Journal of Fish Biology - Journal of Fish Biology (Wiley, 2026)
The Journal of Fish Biology is a leading international journal for scientists engaged in all aspects of fishes and fisheries research, both fresh water and marine. The journal publishes high-quality papers relevant to the central theme of fish biology and aims to bring together under one cover an overall picture of the research in progress and to provide international communication among researchers in many disciplines with a common interest in the biology of fish.
FI 0.63
Q2
Keywords: Agriculture; Aquaculture & Food Science; Aquaculture; Fisheries & Fish Science; Acuicultura; Pesca; Ictiología; Acuerdos transformativos; Transformative agreements; Ecosistemas acuáticos; Biología; Ecología